On the uniqueness of the Dongal type sites - Loman, V.G. (KU Publ., 2021)
To solve a number of problems in the ancient history of not only Kazakhstan, but also the adjacent regions, it is extremely important to study the sites of the period of transition from the Bronze Age to the Early Iron Age. The range of such sites includes the settlement of Dongal, located 208 km southeast of the city of Karaganda (Karkaraly district, Karaganda region), which was explored by an archaeological expedition of the Karagandy University of the name academician E.A. Buketov. Excavations have revealed the preserved lower parts of the walls of the dwellings, formed by horizontal laying of flat stones. Due to this, it was established that the dwellings had a rectangular shape, the walls were lined with stone slabs from the inside. In the center of each building was a hearth, which was a pit surrounded by stone blocks along the perimeter. Utility and pillar pits were located on the floor. The entrances to the dwellings were in the form of an L-shaped corridor. The discovered inventory includes various stone (pestles, graters, polishers, scrapers), bone (scutchers) and bronze (rivets, a fragment of a knife) tools. An archaeozoological analysis of the found animal bones showed that horse breeding was the leading branch of the economy of the inhabitants of the settlement. In the second place was the breeding of cattle, in the third — sheep breeding. Ceramics and the inventory of the settlement have analogies in the settlements of the Sargary-Alekseevsk culture of the Late Bronze Age. At the same time, the essential distinctive features of housebuilding and the ceramic complex allowed the author to single out sites like Dongal into a special type related to the common steppe cultures during the transition from the Final Bronze Age to the Early Iron Age. It is possible that it is on the basis of this community that the cultures of the Scythian-Saka world develop.
Доңғал типіндегі ескерткіштердің өзіндік ерекшелігі туралы
О своеобразии памятников донгальского типа
Keywords: Bronze Age; Early Iron Age; transition period; Sargary-Alekseevsk culture; ceramics; Dongal type; settlement; dwelling